Word Games, Riddles and Logic Tests Tax Your Brain and Boost Your English - Wallwork, Adrian (Easy English!, 2018)
This book contains exercises connected with some of the fun or more unusual aspects of the English languageand with games that typically a native English speaker would do. The games have been adapted into a manageable format, but the actual vocabulary contained has not been changed. The types of games include: lateral thinking games, riddles, logic tests, anagrams, palindromes, proverbs, limericks, word ladders, tongue twisters, plus a whole host of other word-related games. Easy English! is a series of books to help you learn and revise your English with minimal effort. You can improve your English by reading texts in English that you might well normally read in your own language e.g. jokes, personality tests, lateral thinking games, wordsearches. doing short exercises to improve specific areas grammar and vocabulary, i.e. the areas that tend to lead to the most mistakes - the aim is just to focus on what you really need rather than overwhelming yourself with a mass of rules, many of which may have no practical daily value Other books in the Easy English!series include: Wordsearches: Widen Your Vocabulary in English Test Your Personality: Have Fun and Learn Useful Phrases Word games, Riddles and Logic Tests: Tax Your Brain and Boost Your English Top 50 Grammar Mistakes: How to Avoid Them Top 50 Vocabulary Mistakes: How to Avoid Them.